Characterization of PLA/PCL/Nano-Hydroxyapatite (nHA) biocomposites prepared via cold isostatic pressing - Solechan, Solechan; Suprihanto, Agus; Widyanto, Susilo Adi; Triyono, Joko; Fitriyana, Deni Fajar; Siregar, Januar Parlaungan; Cionita, Tezara (MDPI, 2023)
Hydroxyapatite has the closest chemical composition to human bone. Despite this, the use of nano-hydroxyapatite (nHA) to produce biocomposite scaffolds from a mixture of polylactic acid (PLA) and polycaprolactone (PCL) using cold isostatic pressing has not been studied intensively. In this study, biocomposites were created employing nHA as an osteoconductive filler and a polymeric blend of PLA and PCL as a polymer matrix for prospective usage in the medical field. Cold isostatic pressing and subsequent sintering were used to create composites with different nHA concentrations that ranged from 0 to 30 weight percent. Using physical and mechanical characterization techniques such as Fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), scanning electron microscopy (SEM), and density, porosity, tensile, and flexural standard tests, it was determined how the nHA concentrations affected the biocomposite’s general properties. In this study, the presence of PLA, PCL, and nHA was well identified using FTIR, XRD, and SEM methods. The biocomposites with high nHA content showed intense bands for symmetric stretching and the asymmetric bending vibration of PO43−. The incorporation of nHA into the polymeric blend matrix resulted in a rather irregular structure and the crystallization became more difficult. The addition of nHA improved the density and tensile and flexural strength of the PLA/PCL matrix (0% nHA). However, with increasing nHA content, the PLA/PCL/nHA biocomposites became more porous. In addition, the density, flexural strength, and tensile strength of the PLA/PCL/nHA biocomposites decreased with increasing nHA concentration. The PLA/PCL/nHA biocomposites with 10% nHA had the highest mechanical properties with a density of 1.39 g/cm3, a porosity of 1.93%, a flexural strength of 55.35 MPa, and a tensile strength of 30.68 MPa.